2022
DOI: 10.3390/app12136670
|View full text |Cite
|
Sign up to set email alerts
|

Hyperparameter Tuning with High Performance Computing Machine Learning for Imbalanced Alzheimer’s Disease Data

Abstract: Accurate detection is still a challenge in machine learning (ML) for Alzheimer’s disease (AD). Class imbalance in imbalanced AD data is another big challenge for machine-learning algorithms working under the assumption that the data are evenly distributed within classes. Here, we present a hyperparameter tuning workflow with high-performance computing (HPC) for imbalanced data related to prevalent mild cognitive impairment (MCI) and AD in the Health and Aging Brain Study-Health Disparities (HABS-HD) project. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 21 publications
(41 reference statements)
0
4
0
Order By: Relevance
“…To deal with detection of diverse patterns across biomarkers, we suggest using different normalization techniques. Furthermore, instead of applying additional methods to deal with severe class imbalances, we suggest optimizing the hyperparameters of the ML models through grid search or cross‐validation to find the appropriate models that work effortlessly with the data of interest [22–24].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To deal with detection of diverse patterns across biomarkers, we suggest using different normalization techniques. Furthermore, instead of applying additional methods to deal with severe class imbalances, we suggest optimizing the hyperparameters of the ML models through grid search or cross‐validation to find the appropriate models that work effortlessly with the data of interest [22–24].…”
Section: Introductionmentioning
confidence: 99%
“…For a new observation, the class with the largest discriminant value is selected.To deal to severe class imbalances, our approach to data analysis utilizes the methods of hyperparameter tuning. Past studies have indicated that model performance could be enhanced using hyperparameter tunning methods[22][23][24]. The training of decision tree and random forest included hyperparameter tuning using grid search technique.…”
mentioning
confidence: 99%
“…Hyperparameter tuning with class weight optimization is an efficient way to handle imbalanced data [98][99][100][101]. Zhang et al [99] proposed an SVM hyperparameter tuning model with high computing performance.…”
Section: Benchmark Imbalanced Datasetsmentioning
confidence: 99%
“…In the following sections of this article, we will discuss the particulars of Stacked Multi-Kernel SVM and Random Forest models, highlighting their unique advantages and reasoning behind choosing them for diabetes identification. We will focus on exploring hyperparameter tuning techniques that illuminate the methodologies used to optimize the efficiency of these models [29]. Through this comprehensive analysis, we aim to provide valuable insights that extend beyond theoretical considerations and have practical applications in the field of diabetes diagnostics.…”
Section: Introductionmentioning
confidence: 99%